Multistage Sonication Effect on the Composition and Properties of Degraded Chitosan Product - Arifin, Nurul Laili; Savitri, Emma; Indah, Anjar; Putra, Fesa; Sumarno, Sumarno (UI Scholars Hub, 2019)
The sonication method randomly breaks polymer chains to produce a varied distribution of products. A scheme with multi-stage sonication steps is proposed to identify oligomers and low molecular weight chitosan based on changes to the degrad-ed product. For each sonication level, 1% (w/v) chitosan in 1% (v/v) aqueous acetic acid was sonicated for 120 min at 60 °C. The products of the sonication treatment were deprotonized by adding an alkali solution, freeze dried and insoluble product re-sonicated until a low molecular weight was produced. Low molecular weight chitosan/insoluble products were character-ized with Fourier-transform infrared spectra (FT-IR) and X-ray diffraction (XRD) to determine the effect of multistage soni-cation on degree of deacetylation (DD) and degree of crystallinity. The viscosity of the average molecular weight of insolu-ble chitosan was estimated by a viscometric method, while the degree of polymerization (DP) of the chitosan oligomers (COS) were determined by end group analysis. The results showed that the molecular weight of insoluble chitosan decreased and reached a limiting value, (Mlim). The percent yield of oligoglucosamine of the soluble products increased with the num-ber of the sonication stages. The degree of crystallinity of insoluble chitosan increased from 19% to 34.14% while the DD decreased from 82% to 78.1%.